How the rich are different: Hierarchical power as the basis of income size and class - Blair Fix (Forum on Capital As Power - Toward a New Cosmology of Capitalism, 2019)
This paper investigates a new approach to understanding personal and functional income distribution. I propose that hierarchical power - the command of subordinates in a hierarchy - is what distinguishes the rich from the poor and capitalists from workers. Specifically, I hypothesize that individual income increases with hierarchical power, as does the share of individual income earned from capitalist sources. I test this idea using evidence from US CEOs, as well as a numerical model that extrapolates the CEO data. The results indicate that income tends to increase with hierarchical power, as does the capitalist composition of income. This suggests that hierarchical power may be a determinant of both personal and functional income.
Keywords: D31; D33; B5; 330; hierarchy; power; functional income distribution; personal income distribution; inequality; capital as power; class